Knowledge, attitudes and practices regarding the prevention of hepatitis B virus infections, in final year college student nurses in Gauteng Province - Satekge, Mpho Margaret (University of Limpopo (Medunsa Campus), 2010)
Introduction: Hepatitis B infection is a serious blood-borne disease caused by the hepatitis B virus (HBV) which attacks the liver, and is the leading cause of liver cancer and cirrhosis of the liver. HBV can be transmitted through exposure to infected blood and human secretions through needle stick / sharps injuries and splashes. Thus nurses are at high risk for HBV infection. The aim of the study: To investigate the knowledge, attitudes and practices (KAP) regarding the prevention of hepatitis B virus infections, in final year college student nurses in Gauteng province. Methods: A cross-sectional quantitative survey on 350 final year nursing students was conducted in three Gauteng province nursing colleges, using an anonymous self administered questionnaire with questions on knowledge, attitudes, and practices regarding HBV. The data were analysed using SPSS (statistical package for social science studies). Results: Of 350 questionnaires distributed, 312 student nurses returned completed forms (response rate: 89.14% [312/350]). The majority were females (86.8% [270/331]) and were below 31 years of age (30.1% [93/309]). The majority (87.6% [271/310]) had good knowledge of the causes and prevention of HBV. The unvaccinated respondents had fairly low positive attitudes, with a mean, mode and median score of 1 (possible score from -4 to +4). The majority (79% [244/310]) practiced good compliance with universal precautions of, and the majority (64.9% [202/311]) were vaccinated. College A displayed significantly higher knowledge (p<0.001), positive attitudes (p=0.001) and safer practices (p<0.001) than college B and C.
Thesis (MPH)--University of Limpopo, 2010.
Keywords: Hepatitis B; Virus infections; Knowledge; Attitude